Persatuan Islam dan Sosio Kultural Masyarakat Lampung Utara - Adilan, Dilan Imam (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The focus of this research is on the people of Talang Harapan, Kotabumi, North Lampung, whose cultural life and religious understanding are still tied to the traditions of their ancestors. Their religious understandings have been experiencing friction with da'wah movement of Islamic Union (Persatuan Islam; PERSIS) which is critical of occultism and local traditions, especially talking about the mixing of culture and religion. Through a new ethnographic method based on qualitative descriptive method, this study shows an alternative da'wah of Islamic Union that utilizes the